-8-5(1+6x)=5(1-6x)2x

Simple and best practice solution for -8-5(1+6x)=5(1-6x)2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8-5(1+6x)=5(1-6x)2x equation:


Simplifying
-8 + -5(1 + 6x) = 5(1 + -6x) * 2x
-8 + (1 * -5 + 6x * -5) = 5(1 + -6x) * 2x
-8 + (-5 + -30x) = 5(1 + -6x) * 2x

Combine like terms: -8 + -5 = -13
-13 + -30x = 5(1 + -6x) * 2x

Reorder the terms for easier multiplication:
-13 + -30x = 5 * 2x(1 + -6x)

Multiply 5 * 2
-13 + -30x = 10x(1 + -6x)
-13 + -30x = (1 * 10x + -6x * 10x)
-13 + -30x = (10x + -60x2)

Solving
-13 + -30x = 10x + -60x2

Solving for variable 'x'.

Combine like terms: -30x + -10x = -40x
-13 + -40x + 60x2 = 10x + -60x2 + -10x + 60x2

Reorder the terms:
-13 + -40x + 60x2 = 10x + -10x + -60x2 + 60x2

Combine like terms: 10x + -10x = 0
-13 + -40x + 60x2 = 0 + -60x2 + 60x2
-13 + -40x + 60x2 = -60x2 + 60x2

Combine like terms: -60x2 + 60x2 = 0
-13 + -40x + 60x2 = 0

Begin completing the square.  Divide all terms by
60 the coefficient of the squared term: 

Divide each side by '60'.
-0.2166666667 + -0.6666666667x + x2 = 0

Move the constant term to the right:

Add '0.2166666667' to each side of the equation.
-0.2166666667 + -0.6666666667x + 0.2166666667 + x2 = 0 + 0.2166666667

Reorder the terms:
-0.2166666667 + 0.2166666667 + -0.6666666667x + x2 = 0 + 0.2166666667

Combine like terms: -0.2166666667 + 0.2166666667 = 0.0000000000
0.0000000000 + -0.6666666667x + x2 = 0 + 0.2166666667
-0.6666666667x + x2 = 0 + 0.2166666667

Combine like terms: 0 + 0.2166666667 = 0.2166666667
-0.6666666667x + x2 = 0.2166666667

The x term is -0.6666666667x.  Take half its coefficient (-0.3333333334).
Square it (0.1111111112) and add it to both sides.

Add '0.1111111112' to each side of the equation.
-0.6666666667x + 0.1111111112 + x2 = 0.2166666667 + 0.1111111112

Reorder the terms:
0.1111111112 + -0.6666666667x + x2 = 0.2166666667 + 0.1111111112

Combine like terms: 0.2166666667 + 0.1111111112 = 0.3277777779
0.1111111112 + -0.6666666667x + x2 = 0.3277777779

Factor a perfect square on the left side:
(x + -0.3333333334)(x + -0.3333333334) = 0.3277777779

Calculate the square root of the right side: 0.572518801

Break this problem into two subproblems by setting 
(x + -0.3333333334) equal to 0.572518801 and -0.572518801.

Subproblem 1

x + -0.3333333334 = 0.572518801 Simplifying x + -0.3333333334 = 0.572518801 Reorder the terms: -0.3333333334 + x = 0.572518801 Solving -0.3333333334 + x = 0.572518801 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = 0.572518801 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = 0.572518801 + 0.3333333334 x = 0.572518801 + 0.3333333334 Combine like terms: 0.572518801 + 0.3333333334 = 0.9058521344 x = 0.9058521344 Simplifying x = 0.9058521344

Subproblem 2

x + -0.3333333334 = -0.572518801 Simplifying x + -0.3333333334 = -0.572518801 Reorder the terms: -0.3333333334 + x = -0.572518801 Solving -0.3333333334 + x = -0.572518801 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.3333333334' to each side of the equation. -0.3333333334 + 0.3333333334 + x = -0.572518801 + 0.3333333334 Combine like terms: -0.3333333334 + 0.3333333334 = 0.0000000000 0.0000000000 + x = -0.572518801 + 0.3333333334 x = -0.572518801 + 0.3333333334 Combine like terms: -0.572518801 + 0.3333333334 = -0.2391854676 x = -0.2391854676 Simplifying x = -0.2391854676

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.9058521344, -0.2391854676}

See similar equations:

| -3+a/4=-4 | | V+4-8=6(v+7)+2(v+5) | | 8(x-7)=-112 | | -12-11d=-10d | | ax+bx=-4 | | X=10x-78 | | 3x+4x=6x-8 | | 2x+5+2x-23=90 | | -5+b/8=-4 | | -7(x+3)=3(-5-2x) | | 19=-3+4(v-6) | | 2(x+3)-3x-7=2 | | x+x+x+16=25 | | 7t+6=8t | | x^2+y^2-2xy=144 | | 2a+4b+a-b+10= | | (3xy^3)-3xy=0 | | z(z-i)=iz+2 | | 7x+12=40+3x | | t/9--118=130 | | -7a+1=8(1-a)+1 | | -7b-7=-b-7 | | (2a-6)(3a-15)=0 | | -2(v-882)=162 | | z(z-i)=je+2 | | -18+35+(17)= | | -2-9r=10+2r+10 | | 20(16x+8)=12 | | 7-10n+5n=18-96 | | x^4-4x^3+4x^2-36x-45=0 | | 3f=8-5f | | 2.1x-8.9=3.9x-8.9-1.8x |

Equations solver categories